2021
DOI: 10.1109/tvcg.2021.3106494
|View full text |Cite
|
Sign up to set email alerts
|

Complex Interaction as Emergent Behaviour: Simulating Mid-Air Virtual Keyboard Typing using Reinforcement Learning

Abstract: Accurately modelling user behaviour has the potential to significantly improve the quality of human-computer interaction. Traditionally, these models are carefully hand-crafted to approximate specific aspects of well-documented user behaviour. This limits their availability in virtual and augmented reality where user behaviour is often not yet well understood. Recent efforts have demonstrated that reinforcement learning can approximate human behaviour during simple goal-oriented reaching tasks. We build on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In this work, we used the data from our user study, which was explicitly recorded for the considered interaction task. However, the obtained torque ranges should be appropriate for related interaction techniques and tasks as well, as was recently shown for the case of mid-air keyboard typing [29]. If major changes to the user model are made, such as modifying the physiology, running CFAT on new reference data is recommended.…”
Section: Cfat: a Methods To Compute Maximum Voluntary Torques Formentioning
confidence: 97%
See 1 more Smart Citation
“…In this work, we used the data from our user study, which was explicitly recorded for the considered interaction task. However, the obtained torque ranges should be appropriate for related interaction techniques and tasks as well, as was recently shown for the case of mid-air keyboard typing [29]. If major changes to the user model are made, such as modifying the physiology, running CFAT on new reference data is recommended.…”
Section: Cfat: a Methods To Compute Maximum Voluntary Torques Formentioning
confidence: 97%
“…The resulting end-effector trajectories follow both Fitts' Law [19] and the 2 /3 Power Law [35]. Lately, Hetzel et al have extended the model from [16] to simulate mid-air keyboard typing, using the same RL method [29].…”
Section: Deep Learning and Muscle Controlmentioning
confidence: 99%
“…The proposed method utilizes deep RL for collision avoidance and is enabled through AR. In addition to providing a framework for safe symbiotic HRI, Hetzel et al [24] demonstrated the potential of RL to improve the performance of mid-air typing. Many studies have been conducted on enhancing the service experience by providing ideal feedback.…”
Section: The Use Of Reinforcement Learning With Extended Realitymentioning
confidence: 99%
“…Deep RL has been used to learn control policies in increasingly complex state-action spaces -such as torque-actuated humanoids [7,18,53,77] and musculoskeletal systems [37,51], as well as eye-hand coordination in typing [31]. Hetzel et al [25] presented an RL agent for simulating joint-controlled movement of hands in typing, however lamenting that while muscle control would have been preferable, they were not able to train a model that had muscles. Moveover, their control problem was not perceptual like ours; their agent state was a vector describing joint kinematics and the position of next target key.…”
Section: Reinforcement Learning -Based User Modellingmentioning
confidence: 99%